MAC Protocol for Data Gathering in Wireless Sensor Networks with the Aid of Unmanned Aerial Vehicles - VLADUTA, A.-V.; PURA, M. L.; BICA, I. (Advances in Electrical and Computer Engineering, 2016)
Data gathering in wireless sensor networks by employing unmanned aerial vehicles has been a subject of real interest in the recent years. While drones are seen as an efficient method of data gathering in almost any environment, wireless sensor networks are the key elements for generating data because they have low dimensions, improved flexibility, decreased power consumption and costs. This paper addresses the communication at the Medium Access Control (MAC) layer between static deployed sensors and a moving drone whose unique role is to collect data from all sensors on its path. The most important part of the proposed protocol consists of prioritizing the sensors in such a manner that each of them has a fair chance to communicate with the drone. Simulations are performed in NS-2 and results demonstrate the capabilities of the proposed protocol.